SOME EXAMPLES OF SUN LEGENDS IN THE LIGHT OF TEXTS - Mahmood, Remziya; Ahmad , Rebar (Humanities Journal of University of Zakho, 2025)
The literature of the ancient peoples of Kurdistan in the pre-Christian eras was closely intertwined with myths, epics, and stories. As humans at the time were unable to explain natural phenomena scientifically, they resorted to interpreting these occurrences through mythology. A myth typically revolves around an event that took place during an era when deities and their powers played a central role, with the notable absence of any mention of an author or writer. The peoples of Kurdistan in general—and the Hurrians and Mitanni in particular—possessed a rich civilization, history, and culture. They are considered among the most ancient and original civilizations. The history of these peoples is replete with myths and epics, which can serve as valuable sources for future generations to better understand their heritage and avoid repeating past mistakes.